Leadership Challenges in Resource-Constrained Residential Construction Projects in Nepal - Sharma, Kusum (My University, 2026)
Nepalese residential construction projects have been found to be subject to chronic constraints such as inadequate finance, labour, materials, machinery, and information. Such project constraints mean that the performance of leadership plays an important role in the progress and success of the project. Even though literature on delays and inefficiency in residential construction projects in Nepal is not new, existing research focuses mostly on the technical and managerial aspects of construction without considering the impact of leadership on project management during resource shortages. The research is concerned with addressing three major issues which include; (i) The leadership problems faced by primary contractors in the presence of certain constraints; (ii) How leaders deal with such constraints; and (iii) The effects of the leadership styles of primary contractors on secondary contractors. The research adopted a qualitative descriptive design, in which data were obtained using open-ended questionnaires targeting those involved in the process of constructing residential buildings. It is evident from the research results that the shortage of money is the major limitation affecting the planning, control, and coordination process to a greater extent compared to other leadership styles. The time constraints, labour uncertainties, and lack of raw material availability force the leader to make reactive decisions rather than strategizing. There are also other secondary contractors such as electricians, plumbers, and suppliers who encounter limitations resulting from dependencies, such as lack of guidance, delays in payments, and insufficient power. The study claims that the behaviour of leaders in this industry is motivated more by external factors than by any theory of leadership. Documenting well, coordinating better, and putting in place necessary institutional checks will help achieve more efficient and effective leadership as well as improve project results.
Keywords: leadership (activity); project management; Nepal; residential environment; strategic leadership; construction industry; managers and executives; Strategic Project Management; Master’s Programme in Industrial Engineering and Management